Biotic Invasions: Ecological Imperialism in New Wave Science Fiction. - Latham, Rob (Yearbook of English Studies, 2007)
This essay examines a spate of SF novels and stories by Thomas M. Disch, J. G. Ballard, and others published during the 1960s and 70s that address imminent threats to human survival. Replacing 1950s-era tales of nuclear annihilation, these texts envisioned less immediate, but no less apocalyptic, scenarios involving the wholesale extinction of life on earth. The discussion attempts to place these works in the larger context of the growth of ecological science and the environmental movement, which inspired specific consciousness-raising efforts such as Disch's 1971 theme anthology The Ruins of Earth, and Susan Glicksohn's ecologically oriented fanzine from the 1970s, Aspidistra. The overall goal of the essay is to see how SF began to take a critical, species-wide view of the technological 'progress' that the genre had traditionally celebrated.